Making Students' Learning Fun and Meaningful through e-EduTour - Soubakeavathi, Rethinasamy; Soo, Ruey Shing; Nurul Huzaimah, Hussien; Keezrawati, Mujan Yusuf; Liyana, Rosli; Joseph, Ramanair (2022)
This paper provides an illustration of a virtual international student mobility module called e-EduTour. The e-EduTour was created based on Fink’s (2003) Significant Learning principles to enhance the learning experiences of undergraduate students taking the English for Global Communication and Strategic Communication degree programmes at the Faculty of Language and Communication, Universiti Malaysia Sarawak (UNIMAS). The e-EduTour module is co-created by the lecturers with their undergraduates, and it is offered virtually to international partner university participants. This unique module includes English lessons, introduction to UNIMAS faculties and facilities, visits to interesting places in Kuching, introduction to Malaysian culture, food, and drinks. Guided by the instructors, the UNIMAS undergraduates create contents for e-EduTour and serve as buddies throughout the virtual programme. The English classes are taught by experienced instructors while the undergraduates act as teaching assistants and provide peer support to participants during the breakout sessions. The undergraduates utilize knowledge learnt in their courses and work as a team to create contents introducing UNIMAS, tourist spots in Kuching, Malaysian culture, and cuisines. The contents are scripted, recorded, and edited collaboratively by the undergraduates and they take turns to host when they are showcased to the participants during the synchronous sessions. The feedback received from the international participants show that the undergraduate buddy support system acted as a catalyst in helping them develop a positive attitude towards English, enhancing their motivation to learn English, boosting their confidence to speak in English, and enriching their cultural experience. In addition, the UNIMAS undergraduates indicated that the e-EduTour was a fun and meaningful learning platform for them to collaborate with peers, learn through experience in a fun and exciting way, as well as foster personal growth. To conclude, the e-EduTour is a holistic international student mobility module that enables the UNIMAS undergraduates to have a significant learning experience by applying and integrating the knowledge learnt in their courses in a new context beyond the classroom while collaborating with local and international students.